Analisis Efektivitas, Efisiensi dan Kontribusi Pajak Daerah dalam Peningkatan Pendapatan Asli Daerah (PAD) Kabupaten Bondowoso - Dania Meriza Vinanda; Arisona Ahmad (Politeknik Negeri Jember, 2022)
This study aims to determine the effectiveness, efficiency, and contribution of regional taxes in increasing Regional Original Income (PAD) in Bondowoso Regency. The source of the data used in this study is secondary data in the form of a Budget Realization Report (LRA) which consists of targets, realizations and collection costs from hotel taxes, restaurant taxes, street lighting taxes, and Bondowoso Regency Original Revenue (PAD). This study uses a descriptive method with a qualitative approach and processes data using an analysis of effectiveness, efficiency and contribution. The results of the research show that hotel taxes, restaurant taxes, and street lighting taxes are very effective and very efficient in increasing Regional Original Income (PAD). Then the contribution results show that hotel taxes, restaurant taxes, and road lighting taxes are very less contributing to the increase in Regional Original Income (PAD) of Bondowoso Regency.